PERAN PENDIDIKAN AGAMA ISLAM DALAM PENGEMBANGAN KURIKULUM BERBASIS KARAKTER DI MADRASAH IBTIDAIYAH - Hendra SH; Sayed (Prodi Pendidikan Guru Madrasah Ibtidaiyah STAIN Teungku Dirundeng Meulaboh, 2024)
Islamic character education in madrasah ibtidaiyah has a strategic role in forming a generation with noble character and adaptive to the challenges of the digital era. This research aims to analyze the concept, implementation, challenges, and strategies for strengthening Islamic character education in madrasah ibtidaiyah in the face of digital technology developments. This study uses a literature review method by utilizing various relevant latest references. The results of the study show that the concept of Islamic character education in madrasas is centered on the integration of Islamic values in the curriculum, madrasah culture, and learning activities. The implementation of Islamic character education is carried out through a holistic approach that involves teaching values, habituating behavior, and using digital technology. However, the main challenges faced are the lack of digital literacy, exposure to negative content, and limitations in the effective use of technology. To overcome this challenge, a strengthening strategy is needed in the form of collaboration between madrasas and parents through Islamic parenting programs, joint supervision, and effective communication. This research contributes to the development of literature on Islamic character education in the digital era and provides practical recommendations for madrasas to strengthen Islamic character education. With a comprehensive approach, madrasah ibtidaiyah can become an institution that is able to produce a generation with Islamic character who is resilient and responsive to the times.